Growth kinetics of tin oxide nanocrystals in colloidal suspensions under hydrothermal conditions - Lee, Eduardo J. H.; Ribeiro, Caue; Longo, Elson [UNESP]; Leite, Edson R. (Elsevier B.V., 2006)
Colloidal suspensions of tin oxide nanocrystals were synthesized at room temperature by the hydrolysis reaction of tin chloride (II), in an ethanolic solution. The coarsening kinetics of such nanocrystals was studied by submitting the as-prepared suspensions to hydrothermal treatments at temperatures of 100, 150 and 200 degrees C for periods between 60 and 12,000 min. Transmission electron microscopy (TEM) was used to characterize the samples (i.e. distribution of nanocrystal size, average particle radius and morphology). The results show that the usual Ostwald ripening coarsening mechanism does not fit well the experimental data, which is an indicative that this process is not significant for SnO2 nanocrystals, in the studied experimental conditions. The morphology evolution of the nanocrystals upon hydrothermal treatment indicates that growth by oriented attachment (OA) should be significant. A kinetic model that describes OA growth is successfully applied to fit the data. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: crystal growth; oriented attachment; hydrothermal treatment; tin dioxide